Neformalna naselja v postsocialističnih mestih - Tsenkova, Sasha (Urbani izziv, 2010)
In some post-communist cities, the formation of informal settlements is a phenomenon associated with the wave of urbanisation of the 1960s and 1970s. Inothers, the phenomenon is connected with the influx of immigrants and refugees in the 1990s. Informal settlement areas are the result of various factors: inadequate spatial planning, outdated and complex legislation, housing policies that do not ensure the provision of affordable housing and outdated public administration structures. Illegal construction practices in urban areas, often due to the lack of a clear system of property rights and urban poverty, have created significant challenges in many cities such as Tirana, Belgrade, Tbilisi and Bucharest. This paper presents a typology of informal settlements in post-communist cities and discusses the interrelated economic, social and environmental challenges associated with this phenomenon.Various types of informal settlements, as well as the evolution of those types, demonstrate the complexity of the problem as well as the need to develop contextually sensitive and diverse solutions. This study presents the emerging related policy responses, including legalisation and inclusion in formal urban planning, the provision of essential social services (e.g., schools and medical clinics), the construction of technical infrastructure (e.g., safe roads, public transit, water and sewage systems) and resettlement programmes as part of social housing. Although these solutions represent various aspects of the policy continuum, they also require significant political will and the financial commitment of central and local institutions to ensure effective implementation.
Keywords: družbena diferenciacija; imigracija; mesta; postsocialistične države; priseljevanje; stanovanjska naselja; tranzicija